A MEMS Resonator as a Power Receiver for Inductively Powered Implantable Sensors. (2015) - Bakula, Marko; Ceyssens, Frederik; Puers, Robert
Abstract: Power transfer by inductive coupling between two L-C resonant tank circuits is commonly used as a powering method for implantable sensor devices. However, mechanical resonators offer a possibility of improved efficiency due to their higher Q. A quartz tuning fork crystal was investigated for this purpose by mounting miniature magnets on its extensions. The capability of electrical power reception from an alternating magnetic field was investigated, along with the possibility of a fully mechanical sensor with acoustic feedback.